Ferroptosis in acute liver Failure: Unraveling the hepcidin-ferroportin axis and therapeutic interventions - Jinyong He; Cong Du; Cuiping Li; Wei Li; Jinlan Qiu; Mingpeng Ma; Yunhao Chen; Qi Zhang (Redox Biology)
Acute liver failure (ALF) represents a critical clinical syndrome marked by massive hepatocyte death and severe functional deterioration. While metabolic dysregulation is a recognized hallmark, the pathophysiological implications of iron metabolism disturbance in ALF progression remain poorly understood, which may unveil novel therapeutic targets. Using clinical samples and preclinical murine models, we identified ferroptosis as a predominant pathological feature in ALF-affected livers. Notably, pharmacological inhibition of ferroptosis significantly attenuated disease progression in experimental ALF. Mechanistically, dysregulation of the hepcidin-ferroportin (FPN) axis drives hepatic iron overload, precipitating ferroptotic cell death in ALF. The anti-rheumatoid arthritis drug auranofin restored hepcidin-FPN axis homeostasis and mitigated liver injury, though concomitant upregulation of proinflammatory cytokines limited its therapeutic potential. Strikingly, mesenchymal stromal cells (MSCs) demonstrated superior therapeutic efficacy, coordinately modulating the hepcidin-FPN axis while suppressing ferroptosis through PI3K/Akt/Nrf2 pathway activation. Our findings not only establish the causal relationship between hepcidin-FPN axis dysfunction and ferroptosis-driven liver injury, but also propose MSC-based therapy as a multifaceted strategy targeting both iron homeostasis and ferroptosis for ALF management.